MODEL PENJAGA GAWANG MENGGUNAKAN BOLA TENIS PADA SISWA EKSTRAKURIKULER FUTSAL SDN CIKUDA 01 - Muhammad Naufal Riandy (Jurnal Pendidikan Jasmani dan Adaptif (JPJA), 2022)
This study uses the ADDIE research method (Analysis, Design, Development, Implementation, Evaluation), a method that first appeared in 1975 which was developed by the center for learning technology at the University of Florida for the United States military service. The goalkeeper is an important player in the defense line. The abilities and skills possessed are needed to guard the goal from the opponent's goal. One of the abilities that a goalkeeper must have is a good reaction. The study began by analyzing the needs of the model to be created. Then the researcher compiled a draft model that was created and redeveloped based on the evaluation results. After the model was validated by futsal experts and goalkeeper coaches, the model was developed to see how far the model could be applied, the results of which were re-evaluated for the advantages and disadvantages of the model created.